Contraception for the Adolescent Patient. Issue 4 (April 2015) - Truehart, Amber; Whitaker, Amy
<x xml:space="preserve">Abstract</x> Importance The United States continues to have one of the highest teen pregnancy rates of all the industrialized nations. Evidence shows that adolescents are using contraceptive methods, but they are using less effective methods and have high rates of discontinuation, and providers may not be identifying adolescents as candidates for long-term methods. Objective This review sought to dispel contraceptive myths. By providing adolescents with accurate information about all contraception options and by focusing on the most effective methods, providers can better counsel their adolescent patients and facilitate choosing the best method for each individual patient. Evidence Acquisition The US Medical Eligibility Criteria for Contraceptive Use, released in 2010 by the Centers for Disease Control and Prevention, is an invaluable resource when considering contraception for any patient. Results Age alone is not a contraindication for any method of contraception. Adolescents are less likely to experience an unintended pregnancy when they use long-acting methods. Conclusions and Relevance Most adolescents are healthy and have no contraindications to any of the available contraceptive methods. Although it is essential to ask the correct screening questions to identify adolescents who have medical illnesses, it is just as important to make sure that, as providers, we do not limit an adolescent's choice because of misconceptions. Target Audience Obstetricians and gynecologists, family physicians, pediatricians, and all clinicians who care for adolescents. Learning Objectives After completing this CME activity, the participant should be able to counsel an adolescent about the full range of contraceptive methods, identify any medical contraindications for specific methods using the US Medical Eligibility Criteria for Contraceptive Use, dispel common myths that may limit adolescents' contraceptive choices, and identify long-acting methods as appropriate and first-line contraceptive options for adolescents.